Pengaruh Audit Tenure, Audit Fee, Rotasi KAP dan Ukuran KAP Terhadap Kualitas Audit: Pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the influence of audit tenure, audit fee, Public Accounting Firm (KAP) rotation, and KAP size on audit quality in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange from 2020-2023. The research utilizes logistic regression analysis to test hypotheses on a sample of 37 companies, resulting in 148 observation points. The findings reveal that audit tenure, audit fee, and KAP rotation significantly influence audit quality, while KAP size shows no significant effect. The study contributes to audit quality literature by providing empirical evidence from the Indonesian market, particularly during a period that includes the COVID-19 pandemic impact. These results suggest that regulatory policies regarding audit engagement periods, fee structures, and mandatory rotation effectively enhance audit quality, though the Big Four versus non-Big Four distinction may be less relevant in determining audit quality outcomes.